MATURATION AND SPAWNING OF CHINESE POMFRET PAMPUS CHINENSIS (EUPHRASEN) FROM ORISSA COAST - Pati, S (Indian Journal of Fisheries, 2011)
Maturity and spawning of Chinese pomfret, Painpus chinensis (Euphrasen) from Orissa coast have been studied. The results have indicated that the species have a restricted spawning period from September to November. The size at first maturity was observed to be 28 cm SL. in females and 26 cm SL. in males. The fish appears to spawn in deeper water along the stretch of Orissa coast extending from River Mahanadi to Subarnarekha